SELF-EDUCATION AS A PEDAGOGICAL PROBLEM - Oleksandr L. Shums’kyi; Ol’ha O. Shums’ka (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология)
The paper substantiates that the radical changes taking place in all spheres of modern society necessitate a revision of the basic requirements for the training of specialists who should be not only highly qualified, but also be prepared for lifelong education. It has been shown that the state regulations and international documents on education define lifelong learning as the main vector of educational development in the 21st century. It has been determined that the achievement of this goal is possible due to the organization of the training process at university, aimed at gradual transition from the traditional educational format in the form of providing students with a set of ready-made knowledge to self-education, which is the highest degree of education. The essence of the key components of the concept “self-education”, i.e. the categories “self-“ and “education” has been disclosed. The essential differences between the concepts “training” and “education” have been explained, namely: the purpose of training is forming utilitarian skills with specific pragmatic goals, and education is aimed at developing a person as an individual, developing his/her spiritual strengths and abilities. Examples of dictionary equivalents of the term “self-education”, which exist in foreign scientific, reference and encyclopedic literature, have been given. The term “self-education” in the context of philosophy, sociology, psychology and pedagogy has been analyzed. It has been ascertained that among contemporary researchers there is no unanimous position on the interpretation of this term as each of them considers it through the lens of a particular aspect. The main approaches to the definition of the concept “self-education” that have developed in Western pedagogical theory have been characterized. It has been substantiated that full-fledged self-education is possible only if self-study and selfeducation are combined. Self-study involves the acquisition of knowledge on the basis of the person’s own aspirations and through self-selected means. Self-improvement is associated with the manifestation of significant willpower, a high degree of self-awareness, perseverance and purposefulness, resulting in the development of the individual’s qualities that determine the sustainable nature of any kind of independent activity. It has been revealed that in modern didactics self-education is defined as an activity process, and activity is defined as the basis of self-education. The differences between the concepts “self-educational activities”, “independent activity” and “independent work” on key features have been outlined, namely: on the source of goals, the level of independence and the definition of the subject of control over the results. It has been proved that the student’s self-educational activity, in contrast to independent activity, goes beyond external goal-setting and control and is implemented in a completely autonomous mode both during training at university and after graduation. The definition of the term “self-education” is given as the individual’s purposeful systematic cognitive activity, in the course of which he/she independently acquires knowledge and improves skills, resulting in the qualitative development of their personality. The need for continuous self-development is the basis of this activity, and a personal educational product, which involves self-mastery of the system of knowledge and ways to acquire it as well as the development of personality and his/her abilities, is the result of this activity. The main characteristics of self-educational activity are motivational activity, internal freedom, purposefulness, ability to independently acquire necessary knowledge, a strong desire for self-improvement.